Detailed characterization of the UMAMIT proteins provides insight into their evolution, amino acid transport properties, and role in the plant. (5th July 2021) - Zhao, Chengsong; Pratelli, Réjane; Yu, Shi; Shelley, Brett; Collakova, Eva; Pilot, Guillaume
Abstract: Amino acid transporters play a critical role in distributing amino acids within the cell compartments and between plant organs. Despite this importance, relatively few amino acid transporter genes have been characterized and their role elucidated with certainty. Two main families of proteins encode amino acid transporters in plants: the amino acid–polyamine–organocation superfamily, containing mostly importers, and the UMAMIT (usually multiple acids move in and out transporter) family, apparently encoding exporters, totaling 63 and 44 genes in Arabidopsis, respectively. Knowledge of UMAMITs is scarce, based on six Arabidopsis genes and a handful of genes from other species. To gain insight into the role of the members of this family and provide data to be used for future characterization, we studied the evolution of the UMAMITs in plants, and determined the functional properties, the structure, and localization of the 47 Arabidopsis UMAMITs. Our analysis showed that the AtUMAMITs are essentially localized at the tonoplast or the plasma membrane, and that most of them are able to export amino acids from the cytosol, confirming a role in intra- and intercellular amino acid transport. As an example, this set of data was used to hypothesize the role of a few AtUMAMITs in the plant and the cell. Abstract : We show that most of the 47 AtUMAMITs mediate amino acid export and localize mainly at the plasma membrane or vacuole. Public data compilation deciphered their phylogeny and protein structure.